The Effect of Leader Member Exchange, Organizational Citizenship Behavior, and Job Crafting on in Role Performance Mediated by Employee Engagement - Ananda, Muh Aril Surya; Nurhayati, Mafizatun; Rahim, Abdul Rahman (International Journal of Applied Management and Business, 2024)
ABSTRACT Purpose – This study aims to analyze the factors that influence performance based on the influence of Leader Member Exchange, Organizational Citizenship Behavior, Job Crafting, Employee Engagement on In Role Performance at KPP Pratama Bantaeng. Methodology/approach – The number of samples in this study consisted of 108 which were proportionally distributed to all work units in KPP Pratama Bantaeng. This research uses quantitative analysis through Structual Equation Modeling Partial least Square (SEM-PLS) which aims to analyze the relationship between variables. Findings – The results showed that Leader Member Exchange and Employee Engagement have an influence on In Role Performance. On the other hand, Organizational Citizenship Behavior and Job Crafting on In Role Performance. Furthermore, Employee Engagement plays a role in mediating the influence between Leader Member Exchange, Organizational Citizenship Behavior and Job Crafting on In Role Performance. ng.